2015
DOI: 10.1177/1933719114542027
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Blastocyst and Sage Media for In Vitro Maturation of Human Immature Oocytes

Abstract: In vitro maturation (IVM) of human oocytes is an attractive alternative to conventional assisted reproductive technology (ART) treatment, as it involves no or minimal ovarian stimulation. Currently, commercialized media specifically designed for IVM are often used. These media are expensive, have limited shelf life, and must be ordered in advance. If standard culture media can be used in place of the specialized IVM media, it would simplify management and make IVM more feasible and more widely employed in ART … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 20 publications
2
27
0
Order By: Relevance
“…A longer incubation time of GV oocytes did not significantly improve the maturation rate. There is no consensus regarding the optimal maturation timing of oocytes in IVM cycles, and various approaches to timing have been reported in experimental studies [ 12 17 ]. However, a previous study showed that the rates of cleavage and blastocyst development in oocytes matured 48 hours after IVM (72.2%, 19.0%) were significantly lower than in those that matured 24 hours after IVM (91.5%, 50.4%) [ 17 ], which agrees with our results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A longer incubation time of GV oocytes did not significantly improve the maturation rate. There is no consensus regarding the optimal maturation timing of oocytes in IVM cycles, and various approaches to timing have been reported in experimental studies [ 12 17 ]. However, a previous study showed that the rates of cleavage and blastocyst development in oocytes matured 48 hours after IVM (72.2%, 19.0%) were significantly lower than in those that matured 24 hours after IVM (91.5%, 50.4%) [ 17 ], which agrees with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have compared the efficacy of different IVM media on immature oocytes obtained from stimulated or non-stimulated cycles. Recently, Pongsuthirak et al [ 12 ] and Pongsuthirak and Vutyavanich [ 19 ] compared MediCult IVM media (Origio) with Sage IVM media (Cooper Surgical), as well as blastocyst and Sage media, in two randomized controlled trials using immature human oocytes obtained during cesarean deliveries. They showed no differences ( p >0.05) in maturation (65% vs. 69%) or fertilization (65.2% vs. 69%) between oocytes in the different media groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several studies have reported in vivo oocyte collection from ovaries during surgery and the performance of the IVM of immature oocytes. In vivo immature oocyte collection also has been reported during Cesarean section for research 38 and during ovarian enucleation for FP. 39 Several reports described cases in which COH was performed before surgery and the mature oocytes were collected in vivo 40 or ex vivo 41,42 for FP.…”
Section: In Vitro Maturation Of Oocytes Collected In Vivo or Ex Vivomentioning
confidence: 99%
“…The denuded oocytes were classified as either mature (MII) or immature (GV or MI) oocytes. Good quality immature oocytes were cultured in blastocyst medium (G-2 v5 Media, Vitrolife, Sweden) (22) supplemented with 75 mIU mL -1 FSH and 75 mIU mL -1 LH (Ferring) at 37 °C in an incubator under 5% CO 2 and 95% air with high humidity. The maturity of the oocytes was assessed using a stereomicroscope (Olympus, Tokyo, Japan) 24 h after IVM.…”
Section: Ivm Icsi and In Vitro Culturementioning
confidence: 99%